(untitled) (Journal of Economic Research & Business Administration, 2016)
The authors of the article consider the importance of state support of agricultural enterprises in the national economy given the socioeconomic characteristics of our country. The analysis and rating of financial rehabilitation have been conducted, that aimed at ensuring stable operation of the subjects of agriculture in the Republic of Kazakhstan.